A política do audiovisual no Brasil : um estudo sobre as coalizões de defesa no período 2003-2010 - Alves, Renan do Prado (Universidade Federal de São Carlos, 2016)
The public-cultural policies, and in the particular the audiovisual policies, gained prominence at the federal level during the administrations of President Luiz Inacio Lula da Silva (2003-2010). This work aimed to answer such questions: who are the political actors to discuss media in Brazil? What do they believe in? What are their interests? And how do the they get united do defend their interests? Among the many debates that took place during this period of time, four of them have happened by mobilizing the actions of groups who gathered around coalitions. The four controversial issues were: the attempt to create the National Cinema and Audiovisual Agency (Ancinav), the debate over installation of the Brazilian Digital TV System, the creation of Brazil Communications Company (EBC, better know as TV Brazil_ and the debate about the technological convergence between electronic media and telecommunications, proposed by the Draft Law nº 29/2007. The theory and method approach adopted in this study is based on Advocacy Coalition Framework proposed by Paul Sabatier, wic featured collaborations in the years of Jenkins-Smith and Weible. That model aims to explain the political process in a holistc manner by taking into account theoretical premises as the existence of subsystems in public policy and the importance of the values and beliefs of the various political actors involved in this process. Data for the analysis come from selected shorthand notes and available in the Chamber of Deputies – who were treated from the perspective of content analysis – as well as another sources such as ministerial speeches and newspaper articles. As a result we present the three mapped coalitions that impige on the political game an seek to perpetuate their beliefs in the modus operandi of making such audiovisual policy.
Keywords: Advocacy coalition framework; Audiovisual; Coalizões de defesa; Política de cultura no Brasil; Política audiovisual; Cultural policies in Brazil; Audiovisual policy; CIENCIAS HUMANAS::CIENCIA POLITICA